To answer this question, we need to know that we can represent, algebraically, two consecutive positive odd numbers as follows:
![2n+1,2n+3](https://img.qammunity.org/2023/formulas/mathematics/college/qts63v3ei55eko8ynbu2wl0jnd8825z1e1.png)
Then, if we have that the product of both consecutive positive odd numbers is 323, then:
![(2n+1)(2n+3)=323](https://img.qammunity.org/2023/formulas/mathematics/college/4sen60x0d2lljft9xo957iqsqlfl4nfdt6.png)
Now, we will need to expand the formula as follows:
![(2n+1)(2n+3)=2n\cdot2n+2n\cdot3+(1)(2n)+1\cdot3](https://img.qammunity.org/2023/formulas/mathematics/college/229wvxiyw2rktr0an9j7oml3l87xqod08a.png)
We applied the FOIL method to expand the expression. Then, we have:
![4n^2+6n+2n+3=4n^2+8n+3](https://img.qammunity.org/2023/formulas/mathematics/college/5pdpg6jjaq00krflqq2um7fqxo4e8cq491.png)
Now, we have:
![4n^2+8n+3=323](https://img.qammunity.org/2023/formulas/mathematics/college/yhhaqllmntd3ien6rqz81z42bthq8mi3le.png)
![4n^2+8n+3-323=0\Rightarrow4n^2+8n-320=0_{}](https://img.qammunity.org/2023/formulas/mathematics/college/7qxr9ejc1fketdat72mqjm5x8xvoixmuhd.png)
We have here a polynomial (a quadratic equation) that we can solve using the quadratic formula:
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a},ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/college/d8qkmmh3mxtoovm8j5ja34n7ks11xlfyof.png)
Then, we have that:
• a = 4
,
• b = 8
,
• c = -320
Then
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}\Rightarrow x=\frac{-8\pm\sqrt[]{8^2-4(4)(-320)}}{2\cdot4}](https://img.qammunity.org/2023/formulas/mathematics/college/41isgkvfsapxpt2xxn80b9gqp2xc5cret3.png)
![\Rightarrow x=\frac{-8\pm\sqrt[]{64^{}-4(4)(-320)}}{2\cdot4}\Rightarrow x=\frac{-8\pm\sqrt[]{64+5120}}{8}](https://img.qammunity.org/2023/formulas/mathematics/college/ea3cxhi9qcoph3x7odu2etwy0jxr0luea2.png)
![x=\frac{-8\pm\sqrt[]{5184}}{8}\Rightarrow x=(-8\pm72)/(8)](https://img.qammunity.org/2023/formulas/mathematics/college/98ptaktpsc42c48y8yphr27kanyt54hpi1.png)
Then, the solutions are:
![x=(-8+72)/(8)\Rightarrow x=(64)/(8)\Rightarrow x=8](https://img.qammunity.org/2023/formulas/mathematics/college/dojknv7r7oeyavk742ruc7p4inom8u6qsx.png)
![x=(-8-72)/(8)\Rightarrow x=-(80)/(8)\Rightarrow x=-10](https://img.qammunity.org/2023/formulas/mathematics/college/7kdxaqaxdncsxz4cvtxc4yqsltlnbjlwun.png)
Therefore, we have two solutions for n, n = 8 or n = -10.
If we substitute the value of n = 8 in the original equations, we have:
![(2n+1)(2n+3)=323\Rightarrow(2\cdot8+1)(2\cdot8+3)=323](https://img.qammunity.org/2023/formulas/mathematics/college/laxl4mohs23vwpqbhcomqu3zu7zp2elvdm.png)
![(16+1)(16+3)=323\Rightarrow17\cdot19=323](https://img.qammunity.org/2023/formulas/mathematics/college/7dirs6zsngezhj1qy8rjbpz7zo6u778smp.png)
If we use the negative value for the solution, we obtain:
![(2(-10)+1)(2(-10)+3)=323\Rightarrow(-20+1)(-20+3)=323](https://img.qammunity.org/2023/formulas/mathematics/college/m87q9z6g8lvn20ud9jp330zzm4vc31xwsx.png)
![-19\cdot-17=323](https://img.qammunity.org/2023/formulas/mathematics/college/jqsbvrld0mh3ikvjmg3pdcukk5cp9uixk1.png)
Since these two numbers are negative, we have that the appropriate solution is n = 8.
Therefore, we have that the smaller of the two numbers is 17:
![17\cdot19=323](https://img.qammunity.org/2023/formulas/mathematics/college/v7xflridqehpi0kpylily6n5ym15i61spu.png)
The numbers 17 and 19 are consecutive positive odd numbers.
In summary, we have that the smaller number is 17.